From the Perspective of Yang Transforming Qi and Yin Forming Shape: The Traditional Chinese Medicine Treatment of Malignant Ascites - Ge, Pengcheng; Zhang, Yami (Journal of Contemporary Medical Practice, 2024)
Malignant ascites (MA) is one of the most common complications in patients with advanced cancer, and its occurrence often indicates that the tumor has progressed to the terminal stage. Due to its significant impact on patients' quality of life and tolerance to subsequent treatments, it has received widespread clinical attention. Western medicine currently lacks effective treatment options for MA, and there are many limitations to clinical applications, resulting in unsatisfactory overall efficacy. MA falls under the category of "phlegm-dampness" in traditional Chinese medicine (TCM), and there is currently a lack of a unified understanding of its pathogenesis and treatment protocols. Our team believes that the development of this disease is closely related to the imbalance of "yang transforming qi, yin forming form." This article will start from the theory of "yang transforming qi, yin forming form" to explore the pathogenesis and clinical treatment of MA in TCM, providing a reference for clinical syndrome differentiation and treatment, with the aim of improving clinical efficacy.